Antifungal-demelanizing properties and RAW264.7 macrophages stimulation of glucan sulfate from the mycelium of the mushroom Ganoderma lucidum - Wan Mohtar, Wan Abd Al Qadr Imad; Viegelmann, Christina; Klaus, Anita; Abdul Halim Lim, Sarina (Korean Society of Food Science and Technology, 2017)
Underutilized mycelium of Ganoderma lucidum BCCM 31549 has been a significant source of a glucan sulfate (GS) possessing therapeutic activities. GS have been evaluated for their antifungaldemelanizing properties and nitrite oxide production from stimulated RAW264.7 macrophages. GS exhibited antifungal activity against Aspergillus niger A60 with a minimum inhibitory concentration of 60 mg/mL and a minimum fungicidal concentration of 100 mg/mL. At 60mg/mL (sublethal) and 30mg/mL (subinhibitory) doses of GS, the mycelium of A. niger A60 was successfully demelanized with a conidiophore head and black pigment reduction. Additionally, GS successfully stimulated RAW264.7 macrophage cells at a concentration of 500 μg/mL to produce 0.45 μM of nitric oxide. The GS-stimulated RAW264.7 macrophages were morphologically similar to those treated with lipopolysaccharide. The results highlight a novel bifunctional property of mycelial GS from G. lucidum.